Predictor of low academic achievement among Dilla university students, southern Ethiopia, 2024 - Kassaw, Chalachew; Demareva, Valeriia (Frontiers in Education, 2024)
In Ethiopia, despite its growing higher education sector, student achievement rates remain concerning low. Understanding the multifaceted factors influencing academic performance is crucial for improving educational equity and quality. This study delves into potential predictors of academic achievement among Ethiopian higher education students, examining individual characteristics, institutional elements, and broader socioeconomic influences.Methodology: This survey enrolled 362 respondents and conducted from December 7, 2023 and January 22, 2024. Simple random sampling, validated assessment tools and online data collection method was employed to select and collect information from respondents. Data entry and analysis was done using Epi-info 7.0 and SPSS 25, respectively. Logistic regression analysis method was used to determine the association of outcome and independent variable.According to the current study result, 166 (45.9%) of them exhibiting GPAs below 3.18.Female gender, social sciences/humanities or business/economics majors, suboptimal class environments, inadequate laboratory facilities, chronic illness, small class sizes, low emotional coping skills, poor academic self-perception, and high social media use emerged as significant predictors of low academic achievement.This study identified factors associated with academic achievement. Female students, optimal learning environments, and smaller class sizes were linked to better performance, while social sciences/humanities or business/economics, inadequate facilities, and high social media use increased the risk of low achievement. Personal characteristics like emotional coping, selfperception, and chronic illness also played a role. These findings suggest interventions targeting individual and environmental factors could improve student outcomes.